Pemanfaatan Teknologi IoT untuk Optimalisasi Energi dan Manajemen Fasilitas Berkelanjutan Menggunakan Fuzzy Logic - Ceorido Ghalib Wibowo; Jumanto Unjung; Dwika Ananda Agustina Pertiwi; Much. Aziz Muslim (Prosiding SISFOTEK, 2025)
The development of the smart airport concept requires the integration of digital technologies to enhance operational efficiency, environmental sustainability, and passenger comfort. One of the key technologies driving this transformation is the Internet of Things (IoT), which enables real-time data collection and analysis from interconnected devices and sensors. This study explores the utilization of IoT for energy optimization and sustainable facility management in smart airports, focusing on systems such as energy consumption monitoring, automated lighting control, sensor-based temperature regulation, and efficient equipment management. The research employs a literature review and data-driven system analysis within the operational context of modern airports. The results indicate that IoT-based implementations can reduce energy consumption by up to 25–30% through dynamic and predictive control of resource usage. Furthermore, IoT contributes to sustainability by reducing carbon emissions and extending infrastructure lifespan. Therefore, IoT technology serves as a fundamental component in realizing airports that are efficient, environmentally friendly, and future-oriented.